New advancements in the management of Neuromyelitis Optica spectrum disease: literature review - Sudhakar, Padmaja; Abusamra, Khawla; Thandampallayam, Mangayarkarasi; Kini, Ashwini (Frontiers in Ophthalmology, 2023)
Neuromyelitis Optica spectrum disorder (NMOSD) is a relapsing autoimmune disease of the central nervous system (CNS) where aquaporin-4 water channels are the antigenic target of the disease. The spectrum of the disease involves regions of the CNS where the water channel is widely expressed including the spinal cord, the optic nerve, dorsal medulla, brainstem, and thalamus/hypothalamus. Management of NMOSD includes acute as well as long term treatment. Acute symptoms are typically treated with intravenous corticosteroids and/or plasma exchange while long-term treatment involves the use of immunosuppression/immune modulation. The year 2019 is thought to be the “year of the NMOSD” as three new medications became available for this devastating disease. In this review, FDA approved NMOSD medications are discussed.